Classification of semiconducting polymeric mesophases to optimize device postprocessing. Issue 23 (17th August 2015) - Snyder, Chad R.; Kline, R. Joseph; DeLongchamp, Dean M.; Nieuwendaal, Ryan C.; Richter, Lee J.; Heeney, Martin; McCulloch, Iain
ABSTRACT Semiconducting polymers form a variety of phases and mesophases that respond differently to postdeposition solvent or thermal treatments. Here it is shown that classification of these materials into their appropriate mesophases can be a useful tool to optimize their thermal postdeposition treatments. Calorimetry is used to quantify differences between materials having similar molecular structures, using a well‐established framework based on the kinetics and thermodynamics of phase changes. By way of example, this classification scheme is used to identify differences in three polymers, poly(3‐hexylthiophene‐2, 5‐diyl) and two isomeric bithiophene–thienothiophene copolymers. It is demonstrated that poly(3‐hexylthiophene) is a "normal" polymer crystal and that the two bithiophene–thienothiophene copolymers have liquid crystalline phases. The different phase structure is notable in light of the molecular similarity of the three polymers and has an impact on the thermal postprocessing conditions that maximize field effect charge carrier mobility in thin film transistor devices. Strong superheating effects are demonstrated for the two bithiophene–thienothiophene copolymers and the impact on annealing is demonstrated using grazing incidence X‐ray diffraction. Some suggestions are also put forth for what post‐processing should be employed for each class of polymer. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 1641–1653